Las técnicas de la lectura y su incidencia en el rendimiento académico en el área de lengua y literatura de los estudiantes de la escuela “Pedro Páez” en la parroquia Eloy Alfaro, provincia de Cotopaxi, en el periodo lectivo 2014-2015 - Soto Changoluisa, Marcela Jhoana (2016)
The current research has as purpose to optimize the quality into education and developing the teaching learning process adequately on pupils of fourth grade at Pedro Páez elementary school located in Latacunga city, province Cotopaxi. The thesis has a huge relevance on educative aspects which allows to manage the reading skills in the Language and literature area it will help on teaching learning process. For that reason it was proposed, the designing and application of reading skills workshop in order to get a cooperative learning. The most important thing about the thesis is that students will build their own knowledge and put in practice in their daily life. The contents written on this research have updated information and suggestions by many education experts allowing the enough developing of teaching methodologies. This will be useful for all at those who be interested on this topic.